Quantification of Flavonoids in Alpinia officinarum Hance. via HPLC and Evaluation of its Cytotoxicity on Human Prostate Carcinoma (LNCaP) and Breast Carcinoma (MCF-7) Cells - Kazemi, Sohrab; Asadi, Farideh; Barari, Ladan; Morakabati, Payam; Jahani, Maryam; Kani, Seyede Narges Mousavi; Soorani, Farangiz; Kolangi, Fatemeh; Memariani, Zahra (Anti-cancer agents in medicinal chemistry, 2022)
Various plant species have been shown to be effective in the prevention or adjuvant therapy of cancer. Alpinia officinarum and its main phytochemicals have also been the subject of several studies for their anticancer properties. The objective of this study is to analyze the extracts of A. officinarum to quantify flavonoids and to evaluate the growth inhibitory effects of the extracts on MCF-7 and LNCaP cells. A. officinarum aqueous and hydroalcoholic extracts were analyzed by using High-Performance Liquid Chromatography (HPLC) for the quantification of three flavonoid compounds. Then, MCF-7, LNCaP, and fibroblast cells were treated with several concentrations (25, 50, 100, 200, and 400 μg/mL) of extracts (24, 48 and 72h). Cell viability was assessed using an MTT assay. Flow cytometry was conducted to evaluate apoptosis. Galangin and kaempferol (3.85 and 1.57 mg/g dry extract) were quantified, respectively, in hydroalcoholic and aqueous extracts using a validated method. The hydroalcoholic extract significantly decreased the viability of MCF-7 (IC50: 43.45μg/mL for 48h) and LNCaP cells (IC50: 168 μg/mL for 48h). The aqueous extract reduced cancer cell viability by more than 50% only at 200 and 400 μg/mL (72 h). Treatment of primary fibroblasts with both extracts showed no significant decrease in cell viability (25-100 μg/mL; 24 and 48h). The hydroalcoholic extract induced a significant increase in apoptotic cells in both MCF-7 and LNCaP cells. Obtained results demonstrated the cytotoxicity of A. officinarum through apoptosis induction in two cancer cell lines. Further investigations are required to determine the underlying apoptotic cell death mechanisms induced by A. officinarum in cancerous cells.